2012
DOI: 10.1002/lary.23590
|View full text |Cite
|
Sign up to set email alerts
|

Improved objective outcomes and quality of life after adenotonsillectomy with inferior turbinate reduction in pediatric obstructive sleep apnea with inferior turbinate hypertrophy

Abstract: Analytical results suggest that AT with concurrent MAIT achieves favorable subjective and objective outcomes in pediatric OSAS with PSAR. We believe that volume reduction of the inferior turbinate plays an important role in treating pediatric OSAS with inferior turbinate hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 21 publications
1
32
1
2
Order By: Relevance
“…6 Another recent study documented objective improvements in physical and emotional symptoms, daytime performance, caregiver concerns, and overall OSA scores when microdebrider-assisted inferior turbinoplasty was performed in conjunction with T&A. 7 Finally, the safety of pediatric turbinoplasty with or without adenoidectomy was documented in a recent study. 8 Given the potential benefit of turbinoplasty in select pediatric patients with OSDB, but the concern for posttonsillectomy complications, the question arises as to whether or not T&A should be performed alone or if it can be performed safely with turbinoplasty procedures.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…6 Another recent study documented objective improvements in physical and emotional symptoms, daytime performance, caregiver concerns, and overall OSA scores when microdebrider-assisted inferior turbinoplasty was performed in conjunction with T&A. 7 Finally, the safety of pediatric turbinoplasty with or without adenoidectomy was documented in a recent study. 8 Given the potential benefit of turbinoplasty in select pediatric patients with OSDB, but the concern for posttonsillectomy complications, the question arises as to whether or not T&A should be performed alone or if it can be performed safely with turbinoplasty procedures.…”
Section: Introductionmentioning
confidence: 97%
“…Aside from adenotonsillar hypertrophy, turbinate hypertrophy (TH) has also been implicated as a source of upper airway obstruction in some patients with obstructive sleep apnea (OSA) . One study of 25 adult patients found TH alone as the source of polysomnography‐confirmed primary snoring or mild OSA .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If CPAP fails, bi-level positive airway pressure (BiPAP) is the next step of treatment. Surgical treatment is an option depending on specifi c situations where the effect of PAP is limited by the obstruction of the upper airways (16,17,18) or when conservative therapy for severe obstructive SAS fails (19,20,21,22,23).…”
mentioning
confidence: 99%